Spectral response change in a quantum well infrared photodetector by using quantum well intermixing - Shin, JC; Choi, WJ; Han, IK; Park, YJ; Lee, JI; Kim, HJ; Choi, JW; Kim, EK (KOREAN PHYSICAL SOC, 2003)
We have studied the change of spectral response in a Quantum Well Infrared Photodetector (QWIP) by using the Impurity Free Vacancy Disordering (IFVD) technique to change the bandgap of GaAs/AlGaAs Multi Quantum-Well (MQW) absorption layer. The fabricated QWIP whose MQW absorption region was intermixed by an IFVD technique showed the maxinium change in spectral response peak from 8 to 10 mm at 10K when compared to a QWIP without intermixing.
Keywords: SIN CAPPING LAYER; BAND